AESTHETIC IN THE SYSTEM OF SOCIAL RELATIONS IN INFORMATION SOCIETY - Мокляк, Л. І. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2016)
The article analyzes the role and place of aesthetic in the system of social relations in the information society.